عوامل الملل الأكاديمي لدى طلبة الجامعة - رضواني, أشواق; وكواك, مريم (University of Eloued جامعة الوادي, 2023)
ملخص الدراسة هدفت الدراسة للكشف عن العوامل المتسببة في الملل الأكاديمي عند طلبة الجامعة، ولتحقيق ذلك اعتمدنا على المنهج المختلط الاستكشافيواستخدمنا أداتين على مرحلتين وعلى عينتين كانت المرحلة الأولى مقابلة مفتوحة على عينة قصدية مكونة من40 طالبا والمرحلة الثانية استبيانا أعددناه على أساس البيانات التي جمعناها من المقابلة وتم توزيعها على عينة حصصيه مكونة من 190طالبا من جامعة حمه لخضر الوادي للموسم الجامعي 2022-2023 وذلك بمراعاة الجنس والتخصص والمستوى التعليمي، وقد توصلت دراستنا بناء على المتوسط الحسابي بعد التبويب والتحليل والترتيب للبيانات أن أهم عوامل ملل الأكاديمي المرتبة في المقدمة هي ساعات الدراسة المتواصلة وشخصية الاستاذ وطرائق التدريس وعدم التواجد مع الاصدقاء في الفصل الدراسي وعدم توفر الإمكانيات اللازمة، كما توصلت إلى أنه توجد اختلافات طفيفة في ترتيب العوامل حسب الجنس والتخصص والمستوى التي تم دراستها وتوصلت الدراسة أيضا إلى جملة من العوامل الإضافية التي جاءت في السؤال المفتوح في الاستبيان منها النقص الشديد في تدفق شبكة الإنترانت داخل الكليات و التسيير الإداري غير المنظم وعدم توفير أماكن الراحة وفي ضوء هذه النتائج قدمنا بعض الاقتراحات المتمثلة في التخفيف من الحجم الساعي للدراسة والرفع من الكفاءات الشخصية للأستاذ واستخدام استراتيجيات حديثة داخل الفصل الدراسي، التجديد المستمر لمحتويات المناهج الدراسية مع اعتماد الجانب التطبيقي بنسبة أكثر من الجانب النظري. Abstract The study aimed to detect the factors causing academic boredom among university students, and to achieve this, we relied on the exploratory mixed approach and used two tools in two stages and on two samples, the first stage was an open interview on an intentional sample of 40 students and the second stage was a questionnaire that we prepared on the basis of the data we collected from the interview and was distributed to a class sample of 190 students from HammaLakedar university of El Oued for the academic season 2022-2023, taking into account gender, specialization and educational level, and our study found based on The arithmetic average after tabulation, analysis and arrangement of data that the most important factors of academic boredom ranked in the foreground are the hours of continuous study, the personality of the professor, teaching methods, not being with friends in the classroom and not having the necessary capabilities, and also found that there are slight differences in the order of factors according to gender, specialization and level that have been studied, and the study also found a number of additional factors that came in the open question in the questionnaire, including the severe lack of Internet flow within colleges In light of these results, we have made some suggestions to reduce the volume of study, raise the personal competencies of the professor, and use modern strategies within the classroomContinuous renewal of the contents of the academic curricula, with the adoption of the applied side more than the theoretical side.
دراسة استكشافية على طلبة جامعة الوادي
مذكرة ماستر في علوم التربية تخصص ارشاد وتوجيه
Keywords: الملل الأكاديمي، l'ennui académique,academic boredom